Qualitative Analysis of the Completeness of Medical Resume Documentation at Dr. Harjono S Regional Public Hospital, Ponorogo Regency - Arfi Prima Kusuma; Ani Rosita (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2024)
A medical resume is a summary of patient care that plays a vital role in administrative, clinical, legal, and hospital accreditation aspects. This document serves as a crucial component in ensuring service quality and acts as legal medical evidence. This study aims to analyze the completeness of medical resume documentation at Dr. Harjono S Regional Public Hospital and identify the contributing factors to incomplete documentation. This research employed a qualitative descriptive method with a cross-sectional approach. Data were collected through observation of 15 inpatient medical resume documents from two departments (Pediatrics and Orthopedics) and interviews with medical record officers. The research instrument included an observation checklist assessing seven documentation components. Results showed that supporting examination results were the most complete component (100%), while patient identity data had the lowest completeness (67%). Contributing factors to incompleteness included high workload, lack of supervision, and low awareness among staff regarding the importance of complete documentation. Moreover, the absence of an internal quality control system was also identified as a challenge. This study recommends enhancing training, conducting regular supervision, and implementing electronic medical record systems to improve documentation quality.